g Gaya Bahasa Sinestesia Pada Lirik Lagu Bahasa Jepang Masa Kini: Gaya Bahasa Sinestesia - dance wamafma (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2024)
ABSTRACT The study entitled "The Use of Synesthesia Language Style in Today's Japanese Song Lyrics": aims to describe and examine the meaning of synesthesia used in Japanese song lyrics since the last thirteen years, starting from 2010 to 2023. Through the distributional study method, the author collects data through note-taking techniques. Synesthesia is an expression phenomenon used for one type of sensation (sense) to another sensation observed through various types of human senses. A song is music, which is rhythmic, melodic, harmonious. The composer usually expresses his thoughts and feelings in such a way that they merge in a whole. Data sources Japanese song lyrics are then divided into two categories, namely romance theme songs and life themes. Synesthesia is categorized as romance as in the song「こんな甘い痛みがこの世界にあるなんて」tells the story of 'the pain that really exists in this world'. The singer seems to express that he feels a very sweet pain because he keeps thinking about his sweetheart and wants to continue to pursue him, through the category of synesthetic life This lyric also means 「苦い青春を捨てても、行こう」The use of the word 苦い nigai or bitter in 苦い青春 nigai seishun, i.e. bitter youth, can be understood as something displeased, distressed, and sad.